2021
DOI: 10.1002/smll.202105881
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation‐Mediated Hydride Precipitation in Zirconium

Abstract: The formation of hydrides challenges the integrity of zirconium (Zr) fuel cladding in nuclear reactors. The dynamics of hydride precipitation are complex. Especially, the formation of the butterfly or bird‐nest configurations of dislocation structures around hydride is rather intriguing. By in‐situ transmission electron microscopy experiments and density functional theory simulations, it is discovered that hydride growth is a hybrid displacive‐diffusive process, which is regulated by intermittent dislocation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The orientation relationship between the new hydride and the matrix is (111) 𝛿 // (0001) 𝛼-Zr and [110] 𝛿 // [1 210] 𝛼-Zr . [17] The reprecipitated hydride alters the growth direction from The dislocation structures formed after hydride dissolution were characterized in situ at high temperatures. Figure 2a shows the microstructures of some hydrides in a grain before heating.…”
Section: Resultsmentioning
confidence: 99%
“…The orientation relationship between the new hydride and the matrix is (111) 𝛿 // (0001) 𝛼-Zr and [110] 𝛿 // [1 210] 𝛼-Zr . [17] The reprecipitated hydride alters the growth direction from The dislocation structures formed after hydride dissolution were characterized in situ at high temperatures. Figure 2a shows the microstructures of some hydrides in a grain before heating.…”
Section: Resultsmentioning
confidence: 99%
“…† Based on our experimental conditions, the electron beam can raise the local temperature just by ∼3 K, which is consistent with previous reports. [30][31][32] Considering that the melting point of PbO is above 1100 K, 13 the electron beam irradiation cannot result in melting of PbO nanoparticles. In addition, the statistical results showed that the average grain sizes of the Sm-PMN-PT powder samples with normal stoichiometry and 5 mol%, 10 mol% and 15 mol% excess PbO were 282, 306, 310 and 308 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The density of the emitted dislocation is proportional to the square of the hydride length [ 42 , 55 ]. Liu et al, further pointed out the key role of dislocations in the regulation of hydride growth via an in situ experiment [ 56 ]. During hydride precipitation, compressive and shear back stresses accumulate inside hydride, while the tensile and shear stress gather in the α-Zr at the front of the interface.…”
Section: Hydride Nucleation and Growth Behaviorsmentioning
confidence: 99%
“… The mechanism of hydride behavior under different dimensions under stress-free conditions [ 6 , 14 , 52 , 56 ]. Reprinted with permission from [ 6 ]; Copyright 2019 Elsevier.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation